2022
DOI: 10.1039/d2gc00541g
|View full text |Cite
|
Sign up to set email alerts
|

Atom-economic synthesis of β-ketosulfones based on gold-catalyzed highly regioselective hydration of alkynylsulfones

Abstract: Gold(I)-catalyzed highly regioselective hydration of alkynylsulfones comprises an efficient 100% atom-economic route to β-ketosulfones. The reaction proceeds under mild mercury-free conditions (Ph3PAuNTf2 0.5–5 mol %, THF, rt or 60 °С),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Which one is a key step of the catalytic reaction? What is the solvent effect in the light of previous reports 15,16 ? Intrigued by α-imino gold carbenes and chemoselectivities, we here performed a systematic theoretical study to provide a better understanding of the intrinsic mechanism for prototypical reactions in this field.…”
Section: Introductionmentioning
confidence: 96%
“…Which one is a key step of the catalytic reaction? What is the solvent effect in the light of previous reports 15,16 ? Intrigued by α-imino gold carbenes and chemoselectivities, we here performed a systematic theoretical study to provide a better understanding of the intrinsic mechanism for prototypical reactions in this field.…”
Section: Introductionmentioning
confidence: 96%
“…[36,37] We have recently shown that alkynylsulfones can be readily hydrated under gold-catalyzed conditions. [38] However, Au-catalyzed oxygen transfer, involving alkynylsulfones, is still an almost unexplored area. In the recent pioneering work focused on O-atom transfer to alkynylsulfones (Scheme 2), [39] Zhang and coworkers reported that these alkynes undergo highly regioselective desulfonylative oxidation by pyridine N-oxides in the presence of gold-based catalysts, followed by overoxidation or cyclopropanation.…”
Section: Introductionmentioning
confidence: 99%
“…Alkynylsulfones – electron‐deficient alkynes bearing accepting sulfone fragments – were recognized as versatile reagents for alkynylations, [26–29] and, in addition, these species are also often used as building blocks in cycloadditions, [30–33] nucleophilic additions, [34,35] or coupling reactions [36,37] . We have recently shown that alkynylsulfones can be readily hydrated under gold‐catalyzed conditions [38] . However, Au‐catalyzed oxygen transfer, involving alkynylsulfones, is still an almost unexplored area.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few gold-catalyzed functionalizations of 1,3-butadiynes can be found in literature and functionalizations using O-nucleophiles are, in contrast to alkyne substrates, rarely know. [22,[39][40][41][42] One of these examples is a cyclization of 1,3-butadiyne developed by Skrydstrup et al in 2010. [20] The two-fold 1,4addition of a bis-nucleophile enables the synthesis of pyrrole or furan derivatives, which are of particular interest due to their biologically activity.…”
Section: Introductionmentioning
confidence: 99%